Medical tourism: Tourist information sources, satisfaction and post behavioral / Nor Adilah Md. Zain...[et al] - Md. Zain, Nor Adilah; Mohd Zahar, Mohd Salehuddin; Hanafiah, Mohd Hafiz; Zulkifly, Muhammad Izzat (Faculty of Hotel Management and Tourism, Universiti Teknologi MARA Selangor, Puncak Alam campus, 2017)
Medical tourism besides others is one of the recognized new niche tourism products that can contribute the economic development of a country including Malaysia. Despite gradually proliferate in term promotion, there still lack of understanding of core creation processes which are dealing with the pre-stage of information seeking, during experiencing the healthcare treatment and after having the treatment among the international medical tourists. In narrowing the existing study gaps, this paper reviews the information sources, medical provider attributes, satisfactions and behaviour intention and proposed the study framework which showing the connection between those variables.